Green Electricity and Heat Generation in Canada: Implications for Russia - Lavrov, Denis A.; Karpova, Svetlana V.; Avdiyskiy, Vladimir I.; Dubova, Svetlana E.; Makar, Svetlana V.; Barmenkova, Natalia A.; Kazakova, Nataliya A.; Kushchev, Nikolay P. (International Journal of Energy Economics and Policy, 2021)
Today, green energy is a new key feature of the energy sectors in developed and dynamically developing economies. It can stimulate the development of small and medium-sized businesses, greatly impacts on nature conservation and generates a strong technological impulse. Canada is known as one of the countries with a highly developed green energy and is considered to use most of its resources efficiently. Russia possesses significant reserves of natural resources and has high potential in the field of green energy production; however, the share of green energy in its energy balance is not high. The authors have compared Canada and Russia in terms of climatic conditions, financial situation, potential for green energy and social attitudes towards green energy, and demonstrated the similarity of the two countries. Having conducted a regression analysis of green energy production, the authors have further analyzed the regional potential for green energy development by comparing energy prices and proved that green energy is cheaper in Canada. Based on the obtained results, the authors have developed a system of recommendations for Russia in the field of green electricity and for both countries in the field of green heating. The main findings include the system of recommendations, the reasons for the reluctance of Russian society to introduce green energy, and a regional analysis of the most suitable regions for green transformation. Keywords: green energy, Russia, Canada, electricity, heating, strategy JEL Classifications: O13; Q42 DOI: https://doi.org/10.32479/ijeep.10972